Saliva and Salivary Diagnostics 2019
DOI: 10.5772/intechopen.85762
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Biomarkers to Assess Breast Cancer Diagnosis and Progression: Are We There Yet?

Abstract: Technological developments are propelling medical diagnostics forward at unprecedented rates. Advancements in genomic, proteomics and cellomics are leading the way for diagnostic tests that will be capable of rapid multi-analyte detection in both laboratory and non-laboratory settings. Currently, proof-of-principle has been demonstrated for salivary biomarkers, whose up and down regulation has been shown to correlate strongly with breast cancer among women. Consequently, the rationale for this chapter is to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Most studies on the analysis of saliva in breast cancer were aimed at identifying biomarkers that can differentiate patients with breast cancer from healthy controls [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ]. Previously, we identified 11 metabolites that allow us to do this with a sensitivity of up to 91% [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies on the analysis of saliva in breast cancer were aimed at identifying biomarkers that can differentiate patients with breast cancer from healthy controls [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ]. Previously, we identified 11 metabolites that allow us to do this with a sensitivity of up to 91% [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…The literature provides data on the study of the composition of saliva in breast cancer [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ]. Saliva biomarkers have been shown to achieve a sensitivity of 73% (72–74) and a specificity of 74% (72–76) in the diagnosis of breast cancer [ 45 ].…”
Section: Introductionmentioning
confidence: 99%
“…A study carried out in 2000 showed that a salivary proteomics-based panel of biomarkers, consisting of ERBB2/HER2, cancer antigen 15-3 (CA15-3), and tumor suppressor oncogene protein 53 ( TP53 /p53), has a potential use in the initial detection and follow-up screening for the detection of BC in women based on ELISA detection [ 222 ]. Today, isotopic labeling coupled with liquid chromatography tandem mass spectrometry (IL-LC-MS/MS) is often used to characterize the salivary protein profiles in BC patients [ 223 ]. Salivary protein biomarkers are known to be useful for discriminating between healthy controls, fibroadenomas and incipient ductal carcinoma lesions [ 224 ], and lymph-node-positive and lymph-node-negative patients with ductal carcinoma [ 225 ], as well as to assess the differences between the salivary protein profiles of HER2/ neu -receptor-positive and HER2/neu-receptor-negative patients [ 226 ].…”
Section: Breast Cancer Investigation In the Multi-omics Eramentioning
confidence: 99%